The Response of Cow Urine Fertilizer and Rice Husk Charcoal to the Growth and Production of Sweet Mustard (Brassica Juncea L.) - Alfarizi Alfarizi; Desi Sri Pasca Sari Sembiring; Najla Lubis (INFOKUM, 2026)
This study aims to determine the response of cow urine liquid organic fertilizer (POC) and the use of rice husk charcoal on the growth and production of sweet mustard plants. This research method uses a Factorial Randomized Block Design (RAK) consisting of 2 factors with 48 plots, namely: The first factor is the provision of rice husk charcoal symbolized by "M" which consists of 4 treatment levels (M0: Topsoil, M1: Topsoil + Compost (1: 1) / Plot, M2: Topsoil + Rice Husk Charcoal (1: 1) / Plot, M3: Topsoil + Rice Husk Charcoal + Compost (1: 1: 1) / Plot). The second factor is the provision of Cow Urine POC symbolized by "P" which consists of 4 treatment levels (P0: 0ml/l/plot, P1: 40ml/l/plot, P2: 80ml/l/plot, P3: 120 ml/l/plot). So there are 16 combinations consisting of 3 replications. The parameters observed in this study were plant height, number of leaves, leaf width, corm diameter, dry weight per plot, and wet weight per plot. The results showed that the application of cow urine fertilizer (POC) and the use of rice husk charcoal as a growing medium significantly affected the growth and yield of sweet mustard greens. The topsoil + rice husk charcoal + compost (1:1:1) growing medium produced the best growth and yield across all observed parameters. The application of cow urine fertilizer (POC) was at a dose of 80–120 ml/L.